Antecedents and Mediators of Academic Satisfaction in Virtual Vocational Training - José María Figueredo; María del Mar Molero-Jurado; María Francisca Vico-Sánchez; Salvador Hilario Alonso-Delgado; José Javier Rosales-Jiménez; María Concepción Torres-Rojas; Amparo Zorrilla-Lozano; María José Segura-Morillas; María del Carmen Pérez-Fuentes (MDPI AG, 2023)
At a time when distance vocational training is on the rise, it seems logical to investigate the variables that can affect the quality of such teaching. The usability of the virtual environment, as well as the behaviour and disposition of the teaching staff, emerge as key factors that influence burnout, engagement, and academic satisfaction. Using a cross-sectional sample of 208 distance vocational training students, the mediating role of burnout and academic engagement in the relationships established between the usability of the virtual environment, teacher support, and academic satisfaction was analysed. On the other hand, multiple regression analyses were carried out in order to investigate the relationships between the challenges and obstacles faced by distance vocational training students and their level of burnout or engagement. Our results confirm the mediating role of academic burnout and engagement in students' academic satisfaction. Regression analyses suggest that the obstacles faced by distance vocational education and training (D-VET) students influence their level of academic burnout or engagement. Our findings are consistent with the current understanding of the role that certain variables play in the well-being of students and which, in turn, influence the quality of teaching.